Diffusion of Assistive Technology Innovations to Support Inclusive Academic Communication in Higher Education: A Case Study at Universitas PGRI Argopuro Jember - Asrorul Mais; Lailil Aflahkul Yaum (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study explores the diffusion of Assistive Technology (AT) innovations in fostering inclusive academic communication for students with disabilities at Universitas PGRI Argopuro Jember. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observations, and document analysis. The findings demonstrate that AT, such as screen readers (JAWS, NVDA, TalkBack) and locally developed applications (SPETRI-DOC MY EARS, PIVE-MY EYES, CEMA, and SPETRIC-Forum Sahabat Tuli), significantly enhance accessibility, independence, and participation among students with visual, hearing, and physical impairments. Guided by Rogers’ Diffusion of Innovations theory, the adoption process was found to follow the stages of innovators, early adopters, early majority, late majority, and laggards. Critical success factors include institutional policy support, educator competencies, student volunteers as mediators, and the contextual relevance of locally tailored applications. Nevertheless, challenges remain, particularly limited funding, insufficient training, and technical accuracy issues in speech-to-text applications. Overall, the study highlights that successful AT diffusion is determined not solely by technological availability but also by the readiness of institutional ecosystems, inclusive campus culture, and sustainable adaptive policies that collectively promote equity in higher education.